Analisis Perbandingan Kualitas Pelayanan Antara Marketplace Shopee Dan Tokopedia Di Kota Sidoarjo - Wilda Sazkia Nuryana; Sonja Andariani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze the comparison of service quality between the Shopee and Tokopedia marketplaces in Sidoarjo City. Customers compare service quality which consists of several dimensions, namely: Tangibles, Reliability, Responsiveness, Assurance and Empathy. The aim of the research is to determine and analyze the differences in service quality between the Shopee and Tokopedia marketplaces in Sidoarjo City. This research uses a quantitative method by collecting data through a questionnaire using Purposive Sampling techniques in sampling, the respondents in the research were 100 respondents with the following criteria: 1) Users of both Shopee and Tokopedia marketplaces who live in Sidoarjo City, 2) Have made transactions on both marketplaces at least 2-3 times a month. The analysis technique used in this research is the Wilcoxon test as an alternative to the paired T-test which is not normally distributed. The results of this study show that: (1) Quality of Service in the tangibles dimension shows that the average results in tangibles are superior to Shopee compared to Tokopedia, (2) Quality of Service in the reliability dimension shows that the average results in reliability are superior to Shopee compared to Tokopedia, (3) The service quality of the responsiveness dimension shows that the average result on responsiveness is superior to Shopee compared to Tokopedia, (4) the quality of service on the assurance dimension shows that the average result on assurance is superior to Shopee compared to Tokopedia, (5) the service quality of the empathy dimension shows the average result on Empathy is superior to Shopee compared to Tokopedia.